Pengaruh Konseling Kelompok dengan Teknik Behavior Contract Untuk Mengatasi Gaming Disorder pada Remaja - Dina Nur Apriliana; Zhila Jannati; Bela Janare Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The rapid development of digital technology has an impact on adolescent behavior, one of which is the emergence of gaming disorder due to excessive use of online games. This phenomenon was found in adolescents in RT 21 Jalan Tegal Binangun who spent an average of 6–7 hours playing games per day, and there was no structured counseling service available. This study aims to determine the level of gaming disorder before and after being provided with group counseling services using the behavior contract technique, and to test the effect of these services on reducing gaming disorder in adolescents. This study used a quantitative approach with a pre-experimental method through a one group pretest-posttest design. The research sample consisted of 8 adolescents selected using a purposive sampling technique. The data analysis technique used a paired sample t-test. The results showed that (1) the average gaming disorder score before treatment (pretest) was 82.25 and (2) decreased after treatment (posttest) to 72.37. The results of the hypothesis test showed a significance value of 0.003 (p < 0.05), indicating a significant difference between before and after treatment. (3) Based on these results, it can be concluded that group counseling services using the behavior contract technique have a significant effect on reducing the level of gaming disorder in adolescents in RT 21 Jalan Tegal Binangun.